Important Factors in the Cognitive Development of Children with Hearing Impairment: Case Studies of Candidates for Cochlear Implants - Nasralla, Heloisa Romeiro; Goffi Gomez, Maria Valéria Schimidt; Magalhaes, Ana Tereza; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2014)
Introduction The factors that affect the development of children with and without hearing disabilities are similar, provided their innate communication abilities are taken into account. Parents need to mourn the loss of the expected normally hearing child, and it is important that parents create bonds of affection with their child.Objective To conduct a postevaluation of the development and cognition of 20 candidates for cochlear implants between 1 and 13 years of age and to observe important factors in their development.Methods The following instruments were used in accordance with their individual merits: interviews with parents; the Vineland Social Maturity Scale; the Columbia Maturity Scale; free drawings; Bender and Pre-Bender testing; and pedagogical tests.Results The results are described.Conclusion Parental acceptance of a child's deafness proved to be the starting point for the child's verbal or gestural communication development, as well as for cognitive, motor, and emotional development. If the association between deafness and fine motor skills (with or without multiple disabilities) undermines the development of a child's speech, it does not greatly affect communication when the child interacts with his or her peers and receives maternal stimulation. Overprotection and poor sociability make children less independent, impairs their development, and causes low self-esteem. Further observational studies are warranted to determine how cochlear implants contribute to patient recovery.
Keywords: deafness; child development; cochlear implantation